Ulnar collateral ligament tear location may affect return-to-sports rate but not performance upon return to sports after ulnar collateral ligament reconstruction surgery in professional baseball players - Erickson, B. J.; Carr, J.; Chalmers, P. N.; Vellios, E.; Altchek, D. W. (The American Journal of Sports Medicine, 2020)
Background: The number of ulnar collateral ligament (UCL) tears in professional baseball players is increasing. UCL reconstruction (UCLR) is the treatment of choice in players with failed nonoperative treatment who wish to return to sports (RTS). It is unknown if UCL tear location influences the ability of players to RTS or affects their performance upon RTS.